2020
DOI: 10.1521/aeap.2020.32.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pre-exposure Prophylaxis (PrEP) Health Care Experiences Among Men Who Have Sex With Men (MSM) Who Live in Rural Areas of the Midwest

Abstract: Most pre-exposure prophylaxis (PrEP) research samples men who have sex with men (MSM) who live in metropolitan cities. There is a limited understanding of the PrEP experiences among rural MSM. Thirty-four semi-structured interviews were conducted to explore the PrEP health care experiences among 34 rural Midwestern MSM. Of the 34 participants, 23 obtained PrEP from their non-primary care provider (PCP). Three themes were present: (1) PrEP is unavailable in rural areas, (2) PrEP is inaccessible in rural areas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
(65 reference statements)
0
29
0
Order By: Relevance
“…A 2020 qualitative study of barriers and facilitators to PrEP for rural MSM in the Midwest also found a need for increased awareness of PrEP, particularly via publicfacing media such as radio and television. 31 Fourth, although stigma may manifest in many ways, this predominantly rural and small urban sample reported low levels of concern about some aspects of stigma concerning PrEP, including discussing PrEP with health care providers and friends, family, or partners discovering PrEP use. Both PrEP initiators and non-initiators expressed low levels of concern in these areas, which may have been affected by survey nonresponse.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A 2020 qualitative study of barriers and facilitators to PrEP for rural MSM in the Midwest also found a need for increased awareness of PrEP, particularly via publicfacing media such as radio and television. 31 Fourth, although stigma may manifest in many ways, this predominantly rural and small urban sample reported low levels of concern about some aspects of stigma concerning PrEP, including discussing PrEP with health care providers and friends, family, or partners discovering PrEP use. Both PrEP initiators and non-initiators expressed low levels of concern in these areas, which may have been affected by survey nonresponse.…”
Section: Discussionmentioning
confidence: 81%
“…A 2020 qualitative study of barriers and facilitators to PrEP for rural MSM in the Midwest also found a need for increased awareness of PrEP, particularly via public-facing media such as radio and television. 31…”
Section: Discussionmentioning
confidence: 99%
“…Negative attitudes of HCW toward PrEP could adversely affect their communication with potential PrEP users 37 or even their own decisions to prescribe PrEP. 38 Depriving eligible MSM from PrEP access because of the anticipated risks of fueling STI infections may not be in the best public health interest. 39 Studies in different nations, such as the US, 35,40 Canada, 35 Kenya, 41 and Belgium 42 demonstrated the importance of capacity development for HCW to enhance PrEP delivery to achieve successful scale up.…”
Section: Discussionmentioning
confidence: 99%
“…43 One most prominent theme of our findings was the affordability of PrEP, which was in line with that of the other studies reported in countries and regions in Europe, 44 Asia, 44,45 and North America. 38,46 Guidelines on PrEP promulgated by WHO have highlighted that equitable access will contribute to reducing health disparity gap. 47 In Hong Kong, the current price of the medication per month is around HK$6000 (∼US$770), 48 and up to $8000-$10,000 (∼US$1025-1280) if check-ups and monitoring are included as in the private sector, 49 which are generally unaffordable.…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts and recordings were reviewed with attention to both the narrative thread and the themes for each narrator. Identi cation of themes is a commonly used method in health research (26,27). Researchers such as the aforementioned typically seek to locate distinct themes across a number of participants.…”
Section: Methodsmentioning
confidence: 99%